In Situ Plating of Mg Sodiophilic Seeds and Evolving Sodium Fluoride Protective Layers for Superior Sodium Metal Anodes. Issue 32 (20th July 2022) - Zhao, Lingfei; Hu, Zhe; Huang, Zhongyi; Tao, Ying; Lai, Wei‐Hong; Zhao, Along; Liu, Qiannan; Peng, Jian; Lei, Yaojie; Wang, Yun‐Xiao; Cao, Yuliang; Wu, Chao; et al.
Abstract: Sodium metal batteries are recognized as promising candidates for next‐generation energy storage devices, as a result of their high energy density, low redox potential, and cheap material price. Na metal anodes, however, generally exhibit notorious problems, including progressively thickened interfaces with active Na loss and Na metal dendrite growth with safety hazards. Herein, a lightweight aerogel consisting of MgF2 nanocrystals grown on a reduced graphene oxide (RGO) aerogel matrix (MgF2 @RGO) is rationally designed as a multifunctional host material for Na metal anodes. The MgF2 nanocrystals can be electrochemically converted in situ into Mg and NaF nanograins during the first Na plating process, in which the Mg works as sodiophilic nucleation seeds for Na plating and NaF plays a key role in suppressing Na dendrite growth. Significantly, the Na metal anodes with the MgF2 @RGO aerogel host deliver significantly enhanced Coulombic efficiency and dramatically improved cycling stability for more than 1600 h. The morphology evolution confirms the advantages of the Na metal anode with the MgF2 @RGO host, which exhibits dense and flat interfaces. By pairing with the Na3 V2 (PO4 )3 cathode, the Na metal batteries achieve stable cycling and good rate capability, suggesting the potential of the Na/MgF2 @RGO anode for practical applications. Abstract : A lightweight MgF2 @RGO aerogel is prepared as a multifunctional host material for sodium metal anodes. The MgF2 nanocrystals can be converted in situ into Mg as sodiophilic nucleation seeds and NaF to construct an inorganic‐rich stable solid electrolyte interface, which synergistically enable ultrastable Na metal anodes with outstanding cycling stability.